GOVERNANCE DAN KEGIATAN EKONOMI MASYARAKAT PERBATASAN TIMOR LESTE – INDONESIA (KASUS DAERAH ENCLAVE OECUSSE DENGAN NUSA TENGGARA TIMUR) - Joao Muni (Faculty of Economics and Business, Universitas Warmadewa, 2019)
East Timor is a new country that has borders borders the sea with Australia and Indonesia, as well as the land border with Indonesia. Land border in the District of Bobonaro Regency, Regency of Belu District of Malacca, Covalima district of Malacca and Belu Oecusse Enclave Area, whereas the land borders with North Central Timor Regency and the Regency of Kupang, with the characteristics of the border region nearly the same or similar. Along the border line of 268.8 km2 potential problems. Mapping of the relationship between the State border management cooperation between East Timor and Indonesia from the perspective of the fulfillment of the economic rights of the Community border indicates the existence of three levels of the dimension of the problem, namely: at the local level, level national and regional/international level. Economic and trade views see the border region as a potential for the creation of a region-based development of trade relations between countries that are mutually beneficial. In view of this difference of various macro and micro economic factors between countries able to provide scenarios that could trigger a growth at the border as a platform for the exchange of production factors of profitable. This paper recommends that in addition to security-defense approach than in the border region with the approach ' core-periphery ', the approach of ' cross-border ' with activities of the economy that are ' complementary ' against the economy the neighboring country is a policy that can be reached by the local authorities in the border region to launch the construction of a welfare-based local economy and development in the border region is left behind. Keywords: Governace; Indonesia-Timor Leste Border; The Economic Activities Of The Community Borders